Using Web-GIS Vicon as a Risk and Disaster Communication Tool (Terr@ Plural, 2022)
Risk and disaster management involves a large amount of data that needs to be collected, processed, and analyzed to become information that results, therefore, in measures to reduce risk and damage. Therefore, this study aims to describe how the macro processes of risk and disaster management are supported using Geographic Information Systems in the Web platform (SIG Web). More specifically, the use of SIG Web VICON as an alternative to improve risk and disaster management actions, especially in the context of disaster risk assessment and communication by the protection and civil defense agencies in Brazil. The contribution of information that the tool provides for the identification, monitoring of threats, response actions, and characterization of vulnerable populations, makes VICON an instrument with high potential to support reducing the impacts caused by disasters.
Keywords: Geographic Information Systems; Risk management; Disasters; Communication; Emergency communication systems